A safety assessment of biological therapies targeting the IL-23/IL-17 axis in inflammatory bowel diseases. Issue 7 (3rd July 2017) - Verstockt, Bram; Deleenheer, Barbara; Van Assche, Gert; Vermeire, Séverine; Ferrante, Marc
ABSTRACT: Introduction : Many different compounds targeting the interleukin 23/17 axis have been developed and successfully studied in several autoimmune diseases, including inflammatory bowel diseases. Nevertheless, interfering with key immunological pathways raises potential safety concerns. This review focuses on the safety profile of these novel biological therapies. Areas covered : A literature search until March 2017 was performed to collect safety data on different compounds targeting this pathway, with emphasis on ustekinumab and secukinumab. Firstly, the authors discuss briefly how genetics can inform about potential safety issues. Secondly, they extensively describe safety issues (common adverse events, infections, malignancies…), immunogenicity, exposure to ustekinumab in specific populations and provide advice for vaccination. Finally, they address safety profiles of secukinumab and other biological targeting the IL-23/17 axis in IBD. Expert opinion : Current evidence suggests that ustekinumab therapy overweigh the potential drug-related risks. Additional safety data beyond randomized-controlled trials, derived from statistically powered, large prospective studies with long-term follow-up are urgently needed to assess the real-life ustekinumab-related risks and to establish the correct position of these novel class of biologicals in IBD treatment. Combining immunomodulators with ustekinumab seems to be safe, though prospective data specifically addressing this topic are currently missing. Similarly, the combination of different biological therapies still has to be studied.